CONTROL OF CACAO POD BORER, CONOPOMORPHA CRAMERELLA SNELLEN ON CACAO PLANTATIONS IN NORTH SULAWESI USING DEGRADABLE POLYMER SLEEVES - Sembel, Dantje T.; Watung, J.; Shepard, Merle; Hamming, Mike; Carner, Garry R. (EUGENIA, 2011)
ABSTRACT Research was aiming to control the cocoa pod borer, Conophomorpha cramerella using different thickness of degradable plastic and regular plastic by sleeving to protect pods. The studies were carried out in abandoned cacao plantation at Sapa, and commercial cacao plantations at Pungkol in the sub-district of South Minahasa in North Sulawesi, Indonesia. Result showed  that sleeving with plastic at different thickness can reduce markedly the infestation by CPB but there was no significant difference between thickness and type of plastic. Between 85 to 95 % of the pods sleeved with degradable and  non- degradable plastic at the commercial cacao plantation  were not damaged by CPB  but 96 % of control (unsleeved pods)  was damaged by CPB. Key words: Conopomorpha cramerella, cocoa plantations, degradable plastic bags